Inference of admixture origins in indigenous African cattle - Kwondo Kim; Donghee Kim; Hanotte, Olivier H.; Lee, Charles; Heebal Kim; Choongwon Jeong (Oxford University Press, 2023)
Present-day African cattle retain a unique genetic profile composed of a mixture of the Bos taurus and Bos indicus populations introduced into the continent at different time periods. However, details of the admixture history and the exact origins of the source populations remain obscure. Here, we infer the source of admixture in the earliest domestic cattle in Africa, African taurine. We detect a significant contribution (up to ∼20%) from a basal taurine lineage, which might represent the now-extinct African aurochs. In addition, we show that the indicine ancestry of African cattle, although most closely related to so-far sampled North Indian indicine breeds, has a small amount of additional genetic affinity to Southeast Asian indicine breeds. Our findings support the hypothesis of aurochs introgression into African taurine and generate a novel hypothesis that the origin of indicine ancestry in Africa might be different indicine populations than the ones found in North India today.